Junebug - Mead, Alice (New York : Farrar, Straus and Giroux, 1995)
An inquisitive young boy who lives with his mother and younger sister in a rough housing project in New Haven, Connecticut, approaches his tenth birthday with a mixture of anticipation and worry.
School Library Journal
Five Owls
Child Study Children's Book Committee
5.5
3-6
Keywords: Single-parent family -- Fiction; Brothers and sisters -- Fiction; Inner cities -- Fiction; Afro-Americans -- Fiction; Single parent family -- Fiction; Brothers and sisters -- Fiction; Inner cities -- Fiction; African Americans -- Fiction